Essays on International Macroprudential Policy Interactions - Granados Castro, Joan Camilo (My University, 2021)
In this dissertation, I study the international interactions of financial regulations and the macroeconomic implications of accounting for the borderless dimension of these policies when designing macroprudential coordinated policy frameworks. In the first chapter, I revise empirically whether there is evidence supporting the existence of strategic policy interactions between regulators based in different economies. I find that, in effect, for some types of economies and instruments, the foreign prudential policies are relevant benchmarks that they consider when adjusting their policies and point that these additional adjustments, or interactions, can generate the scope for policy coordination improvements. In chapter two, I set a theoretical framework for thinking about the international policy macroeconomic spillovers that could justify such interactions. I specify the relevant factors these may depend on, the relevance of these policies for mitigating financial market frictions, and the importance of considering interactions both at the global level, between centers and peripheries, as well as regionally between peripheries alone. In the third chapter, I argue a dynamic setup is necessary for a complete welfare evaluation of potential cooperative setups given the persistence of the effect of policy on the regulated banks. Then I set a dynamic, stochastic, general equilibrium model with multi-peripheral features to study when coordination can be fruitful and when it becomes counterproductive. I obtain the mechanisms driving the potential welfare and financial stability gains of coordination, and generate policy recommendations on when to engage in a cooperative effort and why. I concludethe dissertation mentioning potential extensions of these studies for future work. More specifically, in chapter one, I obtain that domestic policymakers can adjust their macroprudential toolkit depending on whether they perceive positive or negative financial stability spillovers stemming from foreign economies which will be an instrument-specific feature. When the effect is positive the regulators engage in policy substitution efforts and relax their policy stance, choosing to rely on the stricter regulations of other countries. On the contrary, when the potential effect is negative the regulators engage in policy competition and match the foreign policy tightenings with local stricter policies. The former is found between interactions between peer, or similar economies, such as advanced reacting to advanced, or emerging countries reacting to other emerging, while the latter effect is found between interactions of non-similar economies (emerging-to-advanced, and advanced-to-emerging). In chapter two, I set up a three-country center-multiperpheral model, where I model a regulated banking sector in each economy that is subject to financial agency frictions. In that setup the financial center will act as a global creditor which I found will be a key feature in simultaneously dampening the local effects, and increasing the cross-border effects of themacroprudential policies at the center, which jointly will imply important international spillovers towards the emerging economies. I explain how coordinated policies imply a mitigation in the level of interventionism required for the treatmeant of the financial frictions which implies that coordinated policies can be worth pursuing in presence of important implementation costs of the regulations. Finally, in the last chapter, I make a comprehensive welfare comparison of coordinated, semi-coordinated, and decentralized policy frameworks in a multilateral environment, and explain that a necessary condition for policy coordination to be welfare improving is that the financial center acts cooperatively, otherwise policy cooperation becomes counterproductive. I identifytwo mechanisms that generate these welfare gains, namely the cancelation of the incentives to manipulate the global interest rates with policy within a cooperative coalition, and a policy motive for substituting local capital accumulation at the financial center for global intermediation towards the peripheries. I show these mechanisms work better with coalitions where more emerging economies interact cooperatively with the center and provide policy recommendations on when cooperation is worth pursuing.
Thesis (Ph.D.)--University of Washington, 2021
Keywords: Banking Frictions; International Policy Cooperation; Macroprudential Policies; Open Macroeconomics; Economics; Economics